PENGARUH KOMPETENSI DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA MELALUI MOTIVASI (Studi pada Tenaga Kesehatan di RSU Fastabiq Sehat PKU Muhammadiyah Pati) - Sapuan, Mohamad; Soliha, Euis (Jurnal Ilmiah Telaah Manajemen, 2017)
This study aims to examine and analyze whether the effect of competence and job characteristics on performance through the mediation of motivation on Health Workers in RSU Fastabiq Sehat PKU Muhammadiyah Pati. Sampling was done by census of the entire Medicals in RSU Fastabiq Sehat PKU Muhammadiyah Pati totaling 111 respondents. Technical testing of the data used in this study include validity, reliability, coefficient determination test, F test, hypotheses test and mediation test. The results showed that; competence has positive effect and significant on the motivation, job characteristics has positive effect and no significant on the motivation, competence has positive effect and significant on the performance, characteristics of the job has positive effect and not significant on the performance and motivation of positive and significant impact on performance. motivation mediate the competence of the performance, but competence is more effective than a direct effect on performance through motivation as mediation. Keywords: competence, job characteristics, motivation, performance.